Advertising targeting young children: an overview of 10 years of research (2006–2016). Issue 2 (17th February 2019) - De Jans, Steffi; Van de Sompel, Dieneke; Hudders, Liselot; Cauberghe, Veroline
ABSTRACT: A review of 138 published academic articles was conducted to provide an up-to-date and comprehensive overview of academic research of the past decade (2006–2016) on advertising directed to young children up to 12 years old. The research overview resulted in a conceptual framework comprising five research domains that were found to be most prominent. For each of these five domains, an overview, discussion and future research agenda is presented. We conclude that much of the research of the past decade included food advertising and its effects. Progress has been made in the domain of children's advertising processing, specifically with regard to advertising literacy. Despite the growing importance of embedded advertising, many of the new ad formats remain neglected (e.g. native and mobile advertising). Additionally, only a few studies investigated which executional factors (e.g. humour) are effective in advertisements to target children and social influences are also less often considered.